Exploring the Landscape of Operating Room Scheduling: A Bibliometric Analysis of Recent Advancements and Future Prospects - Md Al Amin; Majed Hadid; Adel Elomri; Rabah Ismaen; Ismail Dergaa; Hind Alashi; Amal Jobran Al-Hajaji; Moustafa Alkhalil; Omar M Aboumarzouk; Abdelfatteh EL Omri (Biomedical Engineering and Computational Biology)
Background: Operating Room Scheduling (ORS) is vital in healthcare management, impacting patient outcomes, economics, and the shift to value-based care. The academic literature offers various solutions with distinct pros and cons. Aim: This study aims to (i) outline ORS challenges across surgical specialties; (ii) examine ORS’s impact on healthcare goals, focusing on patient outcomes, value-based care, and economics; (iii) assess academic solutions’ real-world applicability; and (iv) conduct a bibliometric analysis to track ORS research progression, pivotal works, and future directions. Methods: We performed a comprehensive bibliometric analysis using Scopus data. Biblioshiny from Bibliometrix aided data mining and analysis, spanning 2000 to 2023, tracking publication trends, themes, co-occurrence, and co-citation networks. Results: ORS publications steadily rose, notably post-2013, led by developed nations like the UK, Australia, the US, France, and Germany. Key themes included operating rooms, surgery, and humans. Seven primary research routes emerged, covering Surgery Duration, Allocation, Advanced Scheduling Integration, and Patient Flow Optimization. Citation analysis highlighted heuristic algorithms and integer programing as central ORS themes. Conclusion: This study offers a panoramic ORS overview, advocating an integrated approach aligning patient outcomes, economics, and value-based care. Bibliometric analysis charts ORS research evolution guides future research, and holds significance for practitioners, policymakers, and academics, enhancing ORS paradigms and healthcare delivery.